Cripwashing: Undermining Civil Liberties in the Name of Disability Rights in Contemporary Spain - Moscoso Pérez, Melania (Critical Disability Discourses, 2016)
My purpose in this paper is to reflect on the perverse use of the “language of rights.” To do so I will analyze how the discourse of the Disability Rights Movement is being used by the Government of Partido Popular, the conservative party in Spain, to dismantle the young – and still precarious, when compared to the French or German – Spanish welfare system. My reflection will be focused on the abortion law reformation recently undertaken by the Spanish Minister of Justice, Alberto Ruiz Gallardón. I will argue that he is using disability rights to undermine civil liberties in Spain. I will propose that this use reflects a form of “Cripwashing.” I am using cripwashing with the same meaning that the CLAGS website gives for pinkwashing: “using right protections for one group [in this case people with disabilities] to conceal rights and abuses to other people”. Mon intention dans cet article est de réfléchir à l’utilisation perverse du langage des droits. Pour ce faire, je vais analyser comment le discours des droits des personnes handicapées est utilisé par le gouvernement du Partido Popular, le parti conservateur en Espagne, afin de démanteler le système d’aide sociale qui, comparé à celui des Français ou des Allemands, est encore tout jeune et précaire. Je concentrerai ma réflection sur la réforme de la loi sur l’avortement. Cette réforme fut récemment entreprise par le ministre espagnol de la justice, Alberto Ruiz Gallardón. Je soutien qu’il utilise les droits des personnes handicapées pour miner les droits civils en Espagne. Je propose que cette utilisation reflète une forme de «Crip washing.» J’utilise cripwashing dans le même sens que donne le CLAGS au pinkwashing sur son site web: «utiliser la protection des droits pour un groupe [dans ce cas, des personnes ayant des handicaps] to cacher les droits et des abus faits à d’autres personnes».